استعراض خوارزميات كشف الانتحال التقليدية والدلالية - خالد عمر; صبحي الشحنة (Tishreen University, 2017)
In this paper we review and list, the advantages and limitations of the significant effective techniques employed or developed in text plagiarism detection. It was found that many of the proposed methods for plagiarism detection have a weakness points and do not detect some types of plagiarized operations. This paper show a survey about plagiarism detection including several important subjects in plagiarism detection, which is plagiarism definition, plagiarism prevention and detection, plagiarism detection systems, plagiarism detection processes and some of the current plagiarism detection techniques. This paper compares between different plagiarism detection algorithms, and shows the points of weakness, and points of efficiency, and describe the power of semantic plagiarism detection methods, and shows its efficiency in detect plagiarism cases that another plagiarism detection algorithms don't able to detect these cases, that semantic plagiarism detection methods are developed to get rid of traditional weakness points for all plagiarism detection methods have. في هذه الورقة العلمية نستعرض ونسرد ، المزايا والقيود المفروضة على التقنيات الفعالة المهمة التي تم توظيفها وتطويرها لكشف الانتحال في النصوص . وقد تبين أن العديد من الأساليب المقترحة لكشف الانتحال لديها نقاط ضعف وعدم الكشف عن بعض الأنواع من عمليات الانتحال. وتقوم هذه الورقة بدراسة مسحية حول كشف الانتحال بما في ذلك العديد من الموضوعات المهمة في كشف الانتحال، وهي تعريف الانتحال، ومنع الانتحال وكشف الانتحال ، وأنظمة كشف الانتحال، وعمليات كشف الانتحال وبعض تقنيات كشف الانتحال الحالية. تقارن هذه الورقة بين مختلف خوارزميات كشف الانتحال، وتظهر نقاط الضعف، ونقاط القوة، وتوصف قوة خوارزميات كشف الانتحال الدلالية، وتظهر فعالية هذه الخوارزميات في الكشف عن حالات الانتحال لا تستطيع خوارزميات كشف الانتحال الأخرى اكتشافها،حيث أنه تم تطوير خوارزميات كشف الانتحال الدلالية للتخلص من نقاط الضعف التقليدية التي تمتلها جميع خوارزميات كشف الانتحال الأخرى.